Reprogramming of connexin landscape fosters fast gap junction intercellular communication in human papillomavirus-infected epithelia - Gallego, Carmen; Jaracz-Ros, Agnieszka; Laganà, Marta; Mercier-Nomé, Françoise; Domenichini, Séverine; Fumagalli, Amos; Roingeard, Philippe; Herfs, Michael; Pidoux, Guillaume; Bachelerie, Françoise; Schlecht-Louf, Géraldine (Frontiers in Cellular and Infection Microbiology, 2023)
Human papillomaviruses (HPVs) are highly prevalent commensal viruses that require epithelial stratification to complete their replicative cycle. While HPV infections are most often asymptomatic, certain HPV types can cause lesions, that are usually benign. In rare cases, these infections may progress to non-replicative viral cycles associated with high HPV oncogene expression promoting cell transformation, and eventually cancer when not cleared by host responses. While the consequences of HPV-induced transformation on keratinocytes have been extensively explored, the impact of viral replication on epithelial homeostasis remains largely unexplored. Gap junction intercellular communication (GJIC) is critical for stratified epithelium integrity and function. This process is ensured by a family of proteins named connexins (Cxs), including 8 isoforms that are expressed in stratified squamous epithelia. GJIC was reported to be impaired in HPV-transformed cells, which was attributed to the decreased expression of the Cx43 isoform. However, it remains unknown whether and how HPV replication might impact on the expression of Cx isoforms and GJIC in stratified squamous epithelia. To address this question, we have used 3D-epithelial cell cultures (3D-EpCs), the only model supporting the productive HPV life cycle. We report a transcriptional downregulation of most epithelial Cx isoforms except Cx45 in HPV-replicating epithelia. At the protein level, HPV replication results in a reduction of Cx43 expression while that of Cx45 increases and displays a topological shift toward the cell membrane. To quantify GJIC, we pioneered quantitative gap-fluorescence loss in photobleaching (FLIP) assay in 3D-EpCs, which allowed us to show that the reprogramming of Cx landscape in response to HPV replication translates into accelerated GJIC in living epithelia. Supporting the pathophysiological relevance of our observations, the HPV-associated Cx43 and Cx45 expression pattern was confirmed in human cervical biopsies harboring HPV. In conclusion, the reprogramming of Cx expression and distribution in HPV-replicating epithelia fosters accelerated GJIC, which may participate in epithelial homeostasis and host immunosurveillance.